BmC/EBPZ gene is essential for the larval growth and development of silkworm, Bombyx mori - Mei, Xinglin; Huang, Tianchen; Chen, Anli; Liu, Weibin; Jiang, Li; Zhong, Shanshan; Shen, Dongxu; Qiao, Peitong; Zhao, Qiaoling (Frontiers in Physiology, 2024)
The genetic male sterile line (GMS) of the silkworm Bombyx mori is a recessive mutant that is naturally mutated from the wild-type 898WB strain. One of the major characteristics of the GMS mutant is its small larvae. Through positional cloning, candidate genes for the GMS mutant were located in a region approximately 800.5 kb long on the 24th linkage group of the silkworm. One of the genes was BmC/EBPZ, which is a member of the basic region-leucine zipper transcription factor family. Compared with the wild-type 898WB strain, the GMS mutant features a 9 bp insertion in the 3′ end of open reading frame sequence of BmC/EBPZ gene. Moreover, the high expression level of the BmC/EBPZ gene in the testis suggests that the gene is involved in the regulation of reproductionrelated genes. Using the CRISPR/Cas9-mediated knockout system, we found that the BmC/EBPZ knockout strains had the same phenotypes as the GMS mutant, that is, the larvae were small. However, the larvae of BmC/EBPZ knockout strains died during the development of the third instar. Therefore, the BmC/EBPZ gene was identified as the major gene responsible for GMS mutation.